2022
DOI: 10.1021/acsami.1c23055
|View full text |Cite
|
Sign up to set email alerts
|

Electrospinning SA@PVDF-HFP Core–Shell Nanofibers Based on a Visual Light Transmission Response to Alcohol for Intelligent Packaging

Abstract: A naked-eye detector based on a rapid transmittance response to alcohol was designed to offer real-time and reusable detection of fruit freshness. To ensure the hydrophobicity of the fibrous membrane and high light transmission response to alcohol, fluorine-rich poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP) with low refractive index was selected as the shell layer while sodium alginate (SA) and polyvinyl alcohol (PVA) were selected as the core layer for coaxial electrospinning.The core-shell fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…The TEM image of microfibers demonstrated the formation of core–shell structures by coaxial electrospinning (Figure g). This result matched those observed in many earlier studies. , Due to the change of environmental factors such as air humidity during the electrospinning, the surface charge of the Taylor cone would be affected, which might cause the change of diameter ratio (inner diameter/outer diameter) of the core–shell fiber (Figure g). , Figure g showed low light–dark contrast at the boundary of the core to shell in C–P. This result might be due to the atomic number of PHB and PCL which was not much different, resulting in low contrast in the TEM images …”
supporting
confidence: 88%
“…The TEM image of microfibers demonstrated the formation of core–shell structures by coaxial electrospinning (Figure g). This result matched those observed in many earlier studies. , Due to the change of environmental factors such as air humidity during the electrospinning, the surface charge of the Taylor cone would be affected, which might cause the change of diameter ratio (inner diameter/outer diameter) of the core–shell fiber (Figure g). , Figure g showed low light–dark contrast at the boundary of the core to shell in C–P. This result might be due to the atomic number of PHB and PCL which was not much different, resulting in low contrast in the TEM images …”
supporting
confidence: 88%
“…Owing to the large difference between the viscosity and surface tension of TDDA and PHB, the charge attraction on the surface of the Taylor cone will change during the electrospinning, which will have a greater impact on the internal structure of the fiber. 38 TDDA is mostly distributed in a uniform overall diffusion type in the PHB electrospun fibers. This is the same as the TEM of pheromone-loaded cellulose acetate fibers prepared by Hellmann et al 14 Also in their study, the pheromones in the electrospun fibers of polyamide showed phase separation, and their pheromone loading was lower than that of carriers without phase separation.…”
Section: Discussionmentioning
confidence: 97%
“…The obtained fibers demonstrated an improved cell adhesion, flexibility, and stretchability . The recent study utilized hydrophobic poly­(vinylidene fluoride- co -hexafluoropropylene) (PVDF-HFP) as the sheath solution to prepare an ALG complex fiber having a hydrophobic surface, enabling the fiber material to be used as packaging to keep food fresh . Further, nanoparticles and nanosheets can act as fillers to endow PCFs with hierarchical structure and increased performance.…”
Section: Pcf Design and Propertiesmentioning
confidence: 99%
“…37 The recent study utilized hydrophobic poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP) as the sheath solution to prepare an ALG complex fiber having a hydrophobic surface, enabling the fiber material to be used as packaging to keep food fresh. 101 Further, nanoparticles and nanosheets can act as fillers to endow PCFs with hierarchical structure and increased performance. Liimatainen et al prepared anionic polymer solution that consisted silver nanoparticles and anionic cellulose, which was then complexed with cationic cellulose to form PE-PCF.…”
Section: Pcf Design and Propertiesmentioning
confidence: 99%